PENGARUH HIPPOTHERAPY TERHADAP PENINGKATAN KONTROL POSTUR ANAK DENGAN KONDISI CEREBRAL PALSY SPASTIK DIPLEGI - Sari Tri Yulianti (Jurnal Ilmiah Fisioterapi, 2020)
ABSTRACT Background: Cerebral palsy (CP) refers to a group of disorders of the development of movement and posture that are attributed to a non-progressive lesion that occurs in the immature brain. Children with CP have various degrees of impairment of postural control which can limit physical activity and participation in daily life. Clinical observations have suggested that hippotherapy may be an effective strategy for habilitating postural control deficits in children with CP spastic diplegic. However, there is limited research to support this notion. This case study aimed to investigate the effects of hippotherapy on postural control in children with CP spastic diplegic. Methods: Single case study with pre and post test design of a girl with CP spastic diplegic aged 19 years. A hippotherapy protocol was performed for 45 minutes, twice a week, for 3 weeks. Each hippotherapy session consisted stretching, strengthening, and balance activities. Posture Assesment Scale, a criterion-referenced observational measure designed to measure change in the postural control in children with CP spastic diplegic, was chosen as the assessment tool. Results: Upon completion of the 3-week intervention, there was improvement scores in posture assesment scale. The results showed that there was difference score of posture assesment scale on pre hippotherapy (T0=7) and post hippotherapy (T6=9). Conclusion: The results of this study demonstrate that hippotherapy can improve postural control in children with CP spastic diplegic.